A modified unified viscoplasticity model considering time-dependent kinematic hardening for stress relaxation with effect of loading history. (November 2017) - Chen, Wufan; Wang, Fenghua; Kitamura, Takayuki; Feng, Miaolin
Highlights: A modified constitutive model was proposed based on the unified visco-plasticity theory. Both positive and negative strain rate sensitivities with a long holding time can be simulated by the proposed model. Several examples show some potential descriptions and the strong dependence on prior uploading strain rates for relaxation. Parameter selection for the proposed model is discussed in detail. Abstract: By analyzing the simulation results for stress relaxation with Chaboche model, the effect of loading history is discussed. It is revealed that the Chaboche model without static recovery term cannot demonstrate the influence of prior loading strain rates for drop stress during strain holding period. A modified model based on the Chaboche unified viscoplasticity theory is proposed to mainly focus on the remarkable features of the relaxation behavior of materials. Several numerical examples are discussed in detail to show some potential descriptions and the strong dependence on prior uploading strain rates for relaxation. The experiments of two materials Type 304 stainless steel and TIMETAL 21S are selected to verify the feasibility of proposed model. A series of consistent simulation and prediction results are obtained, including the dependence of drop stress on various prior loading strain rates, the effect of different peak stresses or holding strains with the same prior loading strain rate, multi-relaxation with relaxation histories, and cyclic plasticity. Finally, the principle of parameter determination is also discussed. Graphical abstract: The experiments and predictions for multistep relaxation. From the experiments, the relaxation stress value after the second step was higher than that in the first step but a little bit lower than that in the third step. The prediction from the new model was consistent with the experimental results.